Communicative Strategies or Fossilised Forms: Evaluating English in Language-in-Education Policy - Komilie Situmorang (University of Muhammadiyah Purwokerto, 2020)
It is widely known the focus of learning of English in Indonesia has always been centred on to how to gain the native speakers’ proficiency and learners’ successfulness in learning English is measured by how their speech production match those of the native speakers’. As international communication is no longer about the native speakers’ competence but the learners’ ability in switching and adjusting their Englishes to different speakers for different purposes, this may now be problematic and irrelevant. Using document analysis method, this paper examines the focus of teaching English in Indonesia during the past and recent curriculums. The finding shows that the curriculums focus on the fossilised forms rather than the communicative strategies and that they are not relevant to evaluate the international intelligibility as contrasted with their emphasis on gaining global participation. The paper therefore suggests the improvement in the curriculum and proposes to incorporate the communicative strategies in the evaluation.